2014
DOI: 10.7196/samj.8580
|View full text |Cite
|
Sign up to set email alerts
|

Preventing diabetic blindness: A priority for South Africa

Abstract: The prevalence of diabetes in South Africa is increasing rapidly, and diabetes is a significant cause of blindness. Diabetic complications can induce a cycle of poverty for affected families. Early detection of retinopathy and appropriate management can prevent blindness. Screening for retinopathy using a mobile retinal camera is highly cost-effective, with costs of screening and follow-up treatment being less than the expense of one year of a disability grant. Such a programme is a prime example of a 'best bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…3,7,10 A 2010 survey conducted in Cape Town showed that diabetic retinopathy was responsible for 8% of blindness and 11% of severe visual impairment. 15 Loss of vision in patients with diabetes is disabling as it may impair their ability to selfmonitor blood glucose and administer insulin. In addition, it puts them at greater risk of falling and leads to loss of independence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,10 A 2010 survey conducted in Cape Town showed that diabetic retinopathy was responsible for 8% of blindness and 11% of severe visual impairment. 15 Loss of vision in patients with diabetes is disabling as it may impair their ability to selfmonitor blood glucose and administer insulin. In addition, it puts them at greater risk of falling and leads to loss of independence.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Early identification of retinopathy and appropriate management has been shown to prevent or slow the progression to visual impairment and blindness. 7,15 Only 13.6% of patients received an annual eye examination. This finding is unexpected as there is an on-site eye clinic with a senior medical officer in ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…We estimate that the size of this underestimation is modest, however, as it would be dwarfed by the effects on life-years lost, and to a lesser extent also because the potential loss of quality of life is reduced by the effect of the disability weight for T2DM. With approximately 8 000 new cases of diabetes-related blindness each year [ 10 ] and a disability grant of about R12 120 per blind person per year [ 53 ], the SSB tax may potentially save an additional R97 million (USD 8 million) in T2DM-related costs every year.…”
Section: Discussionmentioning
confidence: 99%
“…Digital fundus photography screening is established in many developed countries, and Khan et al [2] have suggested that this is cost-effective in SA. We are pleased to note the recent efforts of Cook and others to highlight and promote screening in SA, [5,6] including quality assurance assessment of the graders of fundus photographs. [7] Unfortunately there are currently virtually no established screening programmes, and patients' systemic control is often poor.…”
Section: Discussionmentioning
confidence: 99%